2017
DOI: 10.3390/ma10121404
|View full text |Cite
|
Sign up to set email alerts
|

Edible Scaffolds Based on Non-Mammalian Biopolymers for Myoblast Growth

Abstract: In vitro meat has recently emerged as a new concept in food biotechnology. Methods to produce in vitro meat generally involve the growth of muscle cells that are cultured on scaffolds using bioreactors. Suitable scaffold design and manufacture are critical to downstream culture and meat production. Most current scaffolds are based on mammalian-derived biomaterials, the use of which is counter to the desire to obviate mammal slaughter in artificial meat production. Consequently, most of the knowledge is related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 35 publications
(62 reference statements)
2
67
0
Order By: Relevance
“…The cells of other marine organisms can also be co-cultured with the scaffold for meat production. Enrione et al (2017) reported the growth of the Mus musculus muscle cells (C2C12) in the scaffold for meat production. A cost effective medium for the culturing of cells and identification of a plasticizer suitable for the type of cell used are necessary for the successful production of in vitro meat.…”
Section: Discussionmentioning
confidence: 99%
“…The cells of other marine organisms can also be co-cultured with the scaffold for meat production. Enrione et al (2017) reported the growth of the Mus musculus muscle cells (C2C12) in the scaffold for meat production. A cost effective medium for the culturing of cells and identification of a plasticizer suitable for the type of cell used are necessary for the successful production of in vitro meat.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to cell seeding, the films were soaked in CaCl 2 solution (70 mM) for 1 h to crosslink the alginate fraction and obtain a non-water-soluble material [8,24].…”
Section: Edible Film Preparationmentioning
confidence: 99%
“…However, more basic research regarding optimization and production of muscle tissue for food products is necessary [7]. To make in vitro meat an economically viable food, it is necessary to investigate three key components, which are animal-free media, scaffolds [8], and bioreactors [9]. That is, methods to produce in vitro meat commonly employ the growth of myoblasts on a scaffold suspended in a serum-free culture medium in a bioreactor [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations